Parameter Populasi Kerang Lumpur Tropis Anodontia edentula Di Ekosistem Mangrove - Natan, Yuliana (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTPopulation Parameters of Tropical Mudflat Clam, (Anodontia edentula) in MangroveEcosystem. Over a 12 months period (Januari 2005 â Desember 2005), population parameters oftropical mudflat clam, (Anodonta edentula) in mangrove ecosystem were determined. Theobjectives of this research were to study population parameters (growth, recruitment patternand mortality) of this tropical mudflat clam. The results showed that asymtotic length (Linfinity) of males, females, also males and females combined were 65.63 mm, 70.88mm and 70.58mm, and the size of males was less than females; annual growth coefficient (K) of males,females, also males and females combined were 1.3, 1.5 and 1.5 respectively, which indicateda fast growth of the clams in relatively short period, which were 2.3 years for the males, 2 yearsfor the females, and 2.1 year for males and females combined. Subsequently, total mortalityrate (Z) of the males, females, also males and females combined were 4.56 Â± 0.31, 4.61 Â± 0.65, and4.95 Â± 0.43. These high rates were caused by the extreme life condition, also by the thin andfragile shells of the clams. Recruitment occurred every month in the males, females, and alsomales and females combined. Overall, there were two unequal pulses. The peaks of males werein June (12.38%) and October (14.77%), while in the females were in April (16.88%) and August(15.12%), and in the males and females combined were in March (12.67%) and May (20.26%).Keywords : Mudflat clam, growth, mortality, recruitment.Kata kunci: Kerang lumpur tropis, pertumbuhan, kematian, rekrutmen